A functional role for AMPK in female fertility and endometrial regeneration. Issue 6 (December 2018) - McCallum, Melissa L; Pru, Cindy A; Smith, Andrea R; Kelp, Nicole C; Foretz, Marc; Viollet, Benoit; Du, Min; Pru, James K
Abstract : Adenosine monophosphate-activated protein kinase (AMPK) is a highly conserved heterotrimeric complex that acts as an intracellular energy sensor. Based on recent observations of AMPK expression in all structures of the female reproductive system, we hypothesized that AMPK is functionally required for maintaining fertility in the female. This hypothesis was tested by conditionally ablating the two catalytic alpha subunits of AMPK, Prkaa1 and Prkaa2, using Pgr-cre mice. After confirming the presence of PRKAA1, PRKAA2 and the active phospho-PRKAA1/2 in the gravid uterus by immunohistochemistry, control ( Prkaa1/2 fl/fl ) and double conditional knockout mice ( Prkaa1/2 d/d ) were placed into a six-month breeding trial. While the first litter size was comparable between Prkaa1/2 fl/fl and Prkaa1/2 d/d female mice ( P = 0.8619), the size of all subsequent litters was dramatically reduced in Prkaa1/2 d/d female mice ( P = 0.0015). All Prkaa1 /2 d/d female mice experienced premature reproductive senescence or dystocia by the fourth parity. This phenotype manifested despite no difference in estrous cycle length, ovarian histology in young and old nulliparous or multiparous animals, mid-gestation serum progesterone levels or uterine expression of Esr1 or Pgr between Prkaa1/2 fl/fl and Prkaa1/2 d/d female mice suggesting that the hypothalamic–pituitary–ovary axis remained unaffected by PRKAA1/2 deficiency. However, an evaluation of uterine histology from multiparous animals identified extensive endometrial fibrosis and disorganized stromal-glandular architecture indicative of endometritis, a condition that causes subfertility or infertility in most mammals. Interestingly, Prkaa1/2 d/d female mice failed to undergo artificial decidualization. Collectively, these findings suggest that AMPK plays an essential role in endometrial regeneration following parturition and tissue remodeling that accompanies decidualization.